(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Pyelonephritis is a non-specific infectious inflammatory disease of the kidneys that affects the renal parenchyma (mainly interstitial tissue), pelvis and calyces.